Epidemiological and Demographic Characteristics of Patients with Traumatic Spinal Injury and Its Neurological Outcome - Shrestha, Sushil; Dhakal, GR; Marasini, RP; Joshi, KM (Nepal Orthopaedic Association Journal, 2021)
Background: The number of traumatic spinal injury reports is growing annually. The epidemiological characteristics of TSI in Nepal differ from those in other countries. Thus, we compiled epidemiological and demographic factors from Nepal to compare with those from other countries. Method: All the admitted cases of traumatic spinal injury over a period of one year (July 2017- June 2018) were studied regarding their variables like age, sex, occupation, etiology of injury, morphology of the spinal injury, neurological level of injury according to American Spinal Injury Association (ASIA) grading. Result: Among the 206 cases studied, 145 were male (70.38%). The mean age of the patients were (40.62 ± 15.2) yrs with the range from 12 yrs to 83 yrs with the maximum number of cases in the age group of 31-40 years (23.3%). Fall from height was the most common cause of injury(72.33%) and lumbar vertebra(42.71%) was the most common involved vertebra and burst fracture(57.76%) was the most common morphology of the fracture. Most of the patients were housewife (19.9%) followed by farmer(18.93%) and student (18.93%). 49.5% of the cases had intact neurology. Multiple vertebra was injured in 27(13.10%) of the cases and 24 cases (11.65%) were associated with injury to other organ. Conclusion: Traumatic spinal injury is an important public health problem and a major cause of morbidity. It is important to understand the epidemiology to implement appropriate preventative measures. Epidemiology in our scenario is different from that in other developed countries, so intervention measures must be established according to population specific characteristics.